Pengaruh Kualitas Layanan dan Store AtmosphereTerhadap Brand Preference Bangi Kopitiam Kelapa Gading - Jepri Antoni; Vina Meliana (UNIVERSITAS KALBIS, 2022)
Indonesia according to data from the National Development Planning Agency in 2018 was 265 million people. Coffee is a major tropical commodity traded worldwide.. This study aims to determine the effect of service quality and store atmosphere on Bangi Kopitiam Kelapa Gading brand preference. This type of research uses a quantitative method that is processed using SPSS version 20. Data collection in this study uses a non-probability sampling method with questionnaires as a tool for data collection. This study used 135 respondents with the criteria of knowing and consuming Bangi Koptiam Kelapa Gading. The results of the hypothesis test show that the service quality variable has a significant effect on brand preference with a significant value of 0.00 < 0.05, the store atmosphere variable affects brand preference with a significant value of 0.00 < 0.05, as well as the service quality and store atmosphere variables significantly. together have an effect on buying interest with a value of fcount > ftable or 50.725 > 3.06. According to the results of the study, the company should maintain the quality of existing services, design a more attractive store atmosphere so that consumers feel comfortable and develop coffee product variants to increase the company's brand preference so that consumers do not doubt the taste of coffee.